Male Students’ Perceptions of the Nursing Profession: A Qualitative Study - Huang J; Sun H; Tian B (Risk Management and Healthcare Policy, 2024)
Jing Huang,1 Hongxia Sun,2 Bei Tian2 1Department of Nursing, Shanghai University of Traditional Chinese Medicine, Shanghai, 201203, People’s Republic of China; 2Department of Nursing, Shanghai Pudong New Area Zhoupu Hospital (Shanghai Health Medical College Affiliated Zhoupu Hospital), Shanghai, 201318, People’s Republic of ChinaCorrespondence: Bei Tian, Department of Nursing, Shanghai Pudong New Area Zhoupu Hospital (Shanghai Health Medical College Affiliated Zhoupu Hospital), No. 1500 Zhou yuan Road, Pudong New District, Shanghai, 201318, People’s Republic of China, Tel +86-18121216302, Email 18121216302@163.comIntroduction: This study aims to explore the thought, feelings and perceptions of male nursing students and male nursing professionals in the nursing profession.Methods: This present study used a qualitative research design to explore the feelings, thoughts, and opinions of male nursing students (first to fourth years) and male nursing professionals about their perception of the nursing profession. The study recruited 11 male nursing students and 11 male nursing professionals using a purposive sampling method. Data were collected via semi-structured individual interviews using qualitative open-ended inquiries consisting of seven questions. The data were analysed using thematic perspectives.Results: The analysis revealed three themes: (a) perceiving gender varieties, (b) taking apparent advantage of masculine characteristics, and (c) taking an equal perspective. Male students’ replies to their professional gender attitudes were that there was no distinct line among the gender-related advantages and disadvantages according to whether they were first to fourth-year students.Conclusion: Male nursing students and professionals believe that nursing is equally appropriate for both men and women, and they could employ masculine characteristics to thrive in their professional development.Keywords: male nurses, professional development, interventional nursing, semi-structured, masculine